Long-term results of cementless femoral reconstruction following intertrochanteric osteotomy - Merle, Christian; Streit, Marcus R.; Innmann, Moritz Maximilian; Gotterbarm, Tobias (International orthopaedics, 2012)
PurposeThe objective of this retrospective cohort study was to assess the long-term outcome of cementless femoral reconstruction in patients with previous intertrochanteric osteotomy (ITO).MethodsWe evaluated the clinical and radiographic results of a consecutive series of 45 patients (48 hips, mean age 50 years) who had undergone conversion hip replacement following ITO with a cementless, grit-blasted, double-tapered femoral component. Clinical outcome was determined using the Harris hip score. Stem survival for different end points was assessed using Kaplan-Meier survivorship analysis.ResultsAt a mean follow-up of 20 (range, 16-24) years, 11 patients (12 hips) had died, and no patient was lost to follow-up. Six patients (six hips) underwent femoral revision, two for infection, three for aseptic loosening and one for periprosthetic fracture. Mean Harris hip score at final follow-up was 78 points (range, 23-100 points). Stem survival for all revisions was 89% (95%CI, 75-95) at 20 years, and survival for aseptic loosening was 93% (95%CI, 80-98).ConclusionsThe long-term results with this type of cementless femoral component in patients with previous intertrochanteric osteotomy are encouraging and compare well to those achieved in patients with normal femoral anatomy.